Chemotherapy cardiotoxicity research in cancer patients: a bibliometric and visual analysis (1994–2024) - Chen, Guoming; Zhou, Huiping; Wang, Chengbin; Qin, Rui; Yang, Qingyi; Hou, Yingyue; Zhang, Meizhen; Zhang, Cheng; Wang, Ning; Feng, Yibin (Frontiers in Oncology, 2025)
BackgroundRecent advancements in medical technology have significantly boosted the survival rates of cancer patients. The potential toxicities that cancer treatments may induce in other areas of the human body have garnered increasing attention. Chemotherapy, a pivotal component of anticancer therapy, heightens the risk of cardiac damage and contributes to various cardiovascular complications. To comprehensively assess the research landscape concerning chemotherapy-induced cardiotoxicity in cancer patients, this study conducted a visual analysis of pertinent articles utilizing bibliometric tools.MethodWe used CiteSpace, VOSviewer, to analyze the temporal and spatial distribution, disciplinary categories, authorship, references, subject terms, and keywords of 4460 articles retrieved from the Web of Science core collection from 1994 to January 21, 2024.ResultsContributions to this field emanated from 100 countries/regions and 4,343 research institutions, with the United States, China, and Italy emerging as the most prolific contributors in terms of publication volume. The Journal of Clinical Oncology emerged as the primary journal in terms of publications and co-citations within this domain, with Bonnie Ky identified as the most prolific author. Common keywords included breast cancer, doxorubicin, heart failure, trial, adjuvant chemotherapy, paclitaxel, and risk. Terms such as echocardiography, nanoparticles, mechanisms, prevention, society, oxidative stress, inflammation, consensus, and global longitudinal strain delineated the current research frontier in this field. Additionally, the study provided a detailed examination of the fundamental aspects of research in this domain. Presently, key research focuses in this area include elucidating the mechanisms of chemotherapy-induced cardiotoxicity, monitoring and evaluating such cardiotoxicity, and developing strategies for its prevention and treatment.ConclusionThis study provides a comprehensive overview of chemotherapy-induced cardiotoxicity research from 1994 to 2024. Future research should prioritize personalized risk assessment and interdisciplinary collaboration to meet the clinical needs of the cardiovascular oncology field.